2006
DOI: 10.4103/0019-5359.26608
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of leflunomide alone and in combination with methotrexate in the treatment of refractory rheumatoid arthritis

Abstract: BACKGROUND: Rheumatoid arthritis patients who develop refractoriness are left with no alternatives other than leflunomide and costly biological response modifiers. Leflunomide, though effective, was associated with adverse events and has not been extensively studied in the Indian population. AIMS: Determination of safety and efficacy of leflunomide alone and if not useful, in combination with methotrexate in patients refractory to conventional disease-modifying agents. SETTING AND DESIGN: Open labeled clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 20 publications
(42 reference statements)
1
1
0
Order By: Relevance
“…Reported AEs suggested that the most significant safety issue of MTX + LEF combination was potential liver toxicity, which was undoubtedly consistent with the real situation of LEF usage in RA treatment (48). In our study, liver abnormalities occurred in 8.9% of the MTX + LEF, which was lower than those reported in several other RCTs in RA (28,29). The result of the previous study found that the incidence of alanine aminotransferase/aspartate aminotransferase elevations increased ∼ 2-5 folds in the combination of MTX and LEF, which depended on the dosages of MTX (48).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Reported AEs suggested that the most significant safety issue of MTX + LEF combination was potential liver toxicity, which was undoubtedly consistent with the real situation of LEF usage in RA treatment (48). In our study, liver abnormalities occurred in 8.9% of the MTX + LEF, which was lower than those reported in several other RCTs in RA (28,29). The result of the previous study found that the incidence of alanine aminotransferase/aspartate aminotransferase elevations increased ∼ 2-5 folds in the combination of MTX and LEF, which depended on the dosages of MTX (48).…”
Section: Discussionsupporting
confidence: 88%
“…During the 24-week trial, the treatment with MTX + HQT resulted in significant improvement in clinical signs and symptoms of RA, including joint pain, joint swelling, morning stiffness duration, and measures of quality-of-life outcome, as well as in many inflammatory indicators, such as CRP, ESR, and the autoantibody RF. Comparing with MTX + LEF (a recommended therapy for refractory RA) (28)(29)(30), MTX + HQT led to a similar improvement in terms of patients achieving ACR20, ACR50, ACR70, cDAI, LDA, and remission responses and to moderate or good improvement in DAS28-CRP. In this pilot study, the combinational therapy of HQT with MTX effectively and safely alleviated symptoms and signs of patients with active RA.…”
Section: Discussionmentioning
confidence: 85%